Living Values parent groups : a facilitator guide - Tillman, Diane (Deerfield Beach, Fla. : Health Communications, 2000)
Balancing an understanding of a set of core values with parenting skills, this book provides a springboard for parent-child development. It is suitable for psychologists and social workers involved in parent groups.
Keywords: Parenting -- Study and teaching; Values -- Study and teaching